Salvaging a tooth by hemisection (Health Renaissance, 2012)
Introduction : Hemisection may be a valuable form of treatment for molar teeth when caries has progressed to the furcation, or where there is an extensive carious lesion extending subgingivally in one area of the root, making it impossible to place an adequate restoration in that area and the root is considered unrestorable. Case Presentation : When one of the roots of a multirooted teeth is beyond the scope of restoration, it becomes imperative to remove the diseased root. This case report is about the use of hemisection procedure which was carried out to salvage the mesial portion of the mandibular right first molar.Conclusion : The use of the procedure of hemisection can successfully eliminate the need for extraction of the whole tooth if only a part of it is unrestorable. Health Renaissance; September-December 2012; Vol 10 (No.3);251-253DOI: http://dx.doi.org/10.3126/hren.v10i3.7057